ANALYSIS OF EMPLOYMENT SENTIMENT IN THE INDONESIAN TELEMATICS FIELD USE MULTINOMIAL NAIVE BAYES AND VECTOR SPACE MODEL - Tomi Herdiawan, Tomi; Tosida, Eneng Tita; Maesya, Aries (Indonesian Operations Research Association (IORA), 2022)
Indonesia in 2030 experienced a demographic bonus in the sense that Indonesia would have far more labor supply than in previous years. Then there is a discourse that this 4.0 industrial revolution will replace a lot of work, especially low-skilled work or does not require special skills and rough jobs replaced by machinery and artificial intelligent (AI). To obtain the value of the percentage of positive, negative and neutral sentiments from the public regarding the impact of the industrial revolution 4 against labor and employment on online news media sites and social media Twitter, the authors conducted a study